Ahmadiyah di Era Reformasi - Saipul Hamdi (Al-Ulum, 2011)
This article examines the complexities surrounding violence by Muslims towards the Ahmadiyya community in Indonesia in its new era of democracy. Violence emerged in 1998 in the post-Suharto era when some Muslim groups, such as Front Pembela Islam (FPI), claimed that Ahmadiyya is a deviant group (aliran sesat) according to Islamic orthodoxy. This article works to understand why and how Ahmadiyya became a target of violent attacks by some Muslim groups in the post-Suharto era by considering the rise of Islamic fundamentalist groups during this time of new-found religious freedom. In doing so, I ask how politics, economy and Islamic theology emerged as significant factors that contributed to the attack. Through identifying particular case studies of attacks in cities across Java and Lombok, I also explore how government creates the policy to find the best solution and how far the effectiveness of this policy to solve the problem.